Student nurse’s health behaviours and attitudes towards being a role model - Harrison, Catherine (2011)
Objective: To assess a range of health behaviours in pre-registration student nurses including physical activity, smoking, alcohol intake and nutrition and to investigate attitudes towards being a role model for their patients. Comparison took place between pre-registration nurses who are overweight and those who are normal weight to see if this affected both their health behaviours and their attitudes towards being a role model.